2023
DOI: 10.1126/science.adf7760
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the genetics of human infertility

Abstract: Reproduction involves a wide range of biological processes, including organ formation and development, neuroendocrine regulation, hormone production, and meiosis and mitosis. Infertility, the failure of reproduction, has become a major issue for human reproductive health and affects up to one in seven couples worldwide. Here, we review various aspects of human infertility, including etiology, mechanisms, and treatments, with a particular emphasis on genetics. We focus on gamete production and gamete quality, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…Particularly, considering the pivotal role of the nervous system in regulating the endocrine system, 23 it remains unclear whether nervous system impairment is implicated in TCSinduced endocrine disruption and the underlying toxic mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, considering the pivotal role of the nervous system in regulating the endocrine system, 23 it remains unclear whether nervous system impairment is implicated in TCSinduced endocrine disruption and the underlying toxic mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, significant knowledge gaps persist regarding the mechanisms of endocrine disruption induced by TCS at environmental concentration levels. Particularly, considering the pivotal role of the nervous system in regulating the endocrine system, it remains unclear whether nervous system impairment is implicated in TCS-induced endocrine disruption and the underlying toxic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility, as a significant issue in human reproductive health, affects approximately one-seventh of couples worldwide [1]. Changing lifestyle habits, environmental pollution, and psychological factors contribute to this growing trend.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is de ned as the failure to achieve pregnancy after 12 months of regular unprotected sexual intercourse [1]. Approximately 85% of infertile couples have an identi able cause: the most common causes are ovulatory dysfunction, male factor infertility and tubal disease,the remaining 15% of infertile couples suffer from "unexplained infertility " [2].A World Health Organization reported that about 17% of people experience infertility and infertility affects 1 in 6 people globally [3].…”
Section: Introductionmentioning
confidence: 99%